2019
DOI: 10.1186/s13018-019-1479-0
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive percutaneous plate osteosynthesis versus intramedullary nail fixation for distal tibial fractures: a systematic review and meta-analysis

Abstract: BackgroundThe treatment for distal tibial fractures remains controversial to date. Minimally invasive percutaneous plate osteosynthesis (MIPPO) and intramedullary nailing (IMN) are well-accepted and effective methods for distal tibial fractures, but these methods were associated with complications. This study aimed to assess and compare the clinical and functional outcomes in patients with distal tibial fractures treated with MIPPO or IMN.MethodsWe systematically reviewed randomized controlled trials (RCTs) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…In recent years, intramedullary nailing (IMN) and minimally invasive plate osteosynthesis (MIPO) have become common fixation methods for distal tibia fractures [ 9 , 10 ]. Our previous study of a meta-analysis based on 13 randomized controlled trials (RCTs) with 924 patients revealed that IMN for distal tibia fractures is associated with a lower risk of wound complications and a shorter time to union than those for MIPO [ 11 ]. IMN insertion comprises the traditional infrapatellar (IP) approach and suprapatellar (SP) approach in the semiextended position.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, intramedullary nailing (IMN) and minimally invasive plate osteosynthesis (MIPO) have become common fixation methods for distal tibia fractures [ 9 , 10 ]. Our previous study of a meta-analysis based on 13 randomized controlled trials (RCTs) with 924 patients revealed that IMN for distal tibia fractures is associated with a lower risk of wound complications and a shorter time to union than those for MIPO [ 11 ]. IMN insertion comprises the traditional infrapatellar (IP) approach and suprapatellar (SP) approach in the semiextended position.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies reported similar AOFAS outcomes in distal tibia fractures treated with IMN and minimally invasive percutaneous plate osteosynthesis. Moreover, our previous study of a meta-analysis on the basis of 13 RCTs with 924 patients indicated that there were no signi cant differences in the AOFAS outcomes between the IMN and minimally invasive percutaneous plate osteosynthesis groups [11]. However, in the current study, we initially used the AOFAS scores to evaluate the functional outcomes of distal tibia fractures using the SP and IP approaches.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, intramedullary nailing (IMN) and minimally invasive plate osteosynthesis (MIPO) have become common xation methods for distal tibia fractures [9,10]. Our previous study of a meta-analysis based on 13 randomized controlled trials (RCTs) with 924 patients revealed that IMN for distal tibia fractures is associated with a lower risk of wound complications and a shorter time to union than those for MIPO [11]. IMN insertion comprises the traditional infrapatellar (IP) approach and suprapatellar (SP) approach in the semiextended position.…”
Section: Introductionmentioning
confidence: 99%
“…There are many different nal management options for open distal tibial fractures after early surgical debridement and fracture stabilization. The extent and condition of soft tissue is a prerequisite for any management options [16,17]. Intramedullary nail is considered the optimal management choice in most case scenario [6,13,18,19], it is capable of providing early weight bearing and lower incidence of malalignment with less interference in the soft tissue of fracture site.…”
Section: Discussionmentioning
confidence: 99%